Metabolism and diabetes in Ramadan fasting: Exploring health trends and relationships through systematic literature network analysis - Baharuddin, Baharuddin; Wijaya, Adi (Narra Sains Indonesia, 2024)
Ramadan fasting is widely acknowledged for its positive impacts on health, yet it also presents inherent risks, prompting a need for comprehensive exploration into its metabolic implications and its effects on diabetes. This study introduces a novel methodology called systematic literature network analysis (SLNA), which merges bibliometric analysis with systematic literature review (SLR). The aim of this study was to examine the global research landscape concerning Ramadan fasting, metabolism, and diabetes. Through the systematic search strategy, 206 relevant documents were analyzed. Through co-occurrence analysis mapping, the study uncovered four distinct cluster groups, revealing intricate relationships and evolving trends within the field. Moreover, the trajectory of research publications on Ramadan fasting from 2001 to 2023 was tracked, highlighting a growing interest in this domain. The bibliometric analysis emphasized a consensus regarding the beneficial effects of Ramadan fasting on individual health, particularly in improving lipid profiles, managing body weight, regulating glucose levels, and nutrient intake. However, significant variations in research focus were observed across predominantly Muslim countries, with notable exceptions like Indonesia and Brunei Darussalam absent among the top contributors. Furthermore, the analysis shed light on the balanced selection of research subjects by authors, indicating a nuanced approach to exploring the multifaceted aspects of Ramadan fasting, metabolism, and diabetes. These findings offer significant perspectives for researchers aiming to contextualize their studies within the wider conversation on this subject, thereby aiding in a more profound comprehension of the intricate relationship between fasting, metabolic functions, and the management of diabetes.